"Like finding a unicorn": Healthcare preferences among lesbian, gay, and bisexual people in the United States. (July 2018) - Martos, Alexander J.; Wilson, Patrick A.; Gordon, Allegra R.; Lightfoot, Marguerita; Meyer, Ilan H.
Abstract: Lesbian, gay, and bisexual (LGB) peoples' healthcare preferences are often developed in response to social and institutional factors that can ultimately deter them from care. Prior qualitative explorations of LGB healthcare preferences have been limited in their ability to identify and compare patterns across age cohort, gender, and race/ethnicity. The current study examines qualitative data from 186 modified Life Story Interviews with three age cohorts of LGB people from New York City, NY, San Francisco, CA, Tucson, AZ, and Austin, TX to understand the factors influencing LGB people's healthcare preferences. Data are analyzed using a directed content analysis approach. Five key themes emerged regarding influences on healthcare preferences: Stigma, provider expertise, identity, service type, and access. Findings suggest that healthcare preferences among LGB people are both complex and closely linked to social changes over time. Healthcare preferences among LGB people are both complex and closely linked to social changes over time. Highlights: Stigma a key consideration for LGB people when weighing healthcare preferences. Identifying LGB-specific clinics and providers a challenge even in urban hubs. Identity-based preferences often associated with type of service being sought. Provider expertise takes precedence among those with chronic health conditions.